Surgical treatment of a Pattern I Obstructive Sleep Apnea Syndrome individual - clinical case report - Christiane Cavalcante Feitoza; Matheus Corrêa da-Silva; Yasmim Lima Nascimento; Elaine Sobral Leite; Corintho Viana Pereira; Lucas Gomes Patrocínio (Sleep Science)
Obstructive Sleep Apnea Syndrome (OSA) is a multifactorial disease that highly alters a persons quality of life. It is characterized by the repeated interruption of breathing during sleep, due to an obstruction or the collapse of the upper airways. Since it is a multifactorial etiological disorder, it requires a thorough diagnosis and treatment with an interdisciplinary team, which comprises several professionals such as a surgical dentist, phonoaudiologist, otorhinolaryngologist, sleep doctor, neurologist and physiotherapist. The diagnosis and the degree of severity of the syndrome is determined through a polysomnography examination. After that, the best form of treatment is devised depending on the gravity of the case. In cases of moderate to severe apnea, invasive treatment through surgical procedures such as maxillomandibular advancement remains the preferred option as it increases the posterior air space, reducing and/or eliminating the obstruction. Thus, improving the patients respiratory function and, consequently, his quality of life as it is shown in the clinical case at hand. In which the male patient, facial pattern type I, 41 years of age, diagnosed with moderate OSA (Apnea-Hypopnea Index - AHI of 23.19), decided to have a surgical treatment instead of a conservative one, resulting in the cure of apnea (AHI of 0.3).